2017
DOI: 10.1177/0886260517691521
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Violence Exposure and Chronic Pain in Adult Sickle Cell Patients

Abstract: Almost half of sickle cell disease (SCD) patients develop chronic, debilitating physical pain with uncertain genesis for which they primarily receive opiate-based palliative treatment. Psychological trauma exposure, especially interpersonal victimization, has been linked to the perception of pain in several medical diseases, but has yet to be examined in SCD patients. This study examines self-reported chronicity of pain and use of prescribed opiates in 50 adult SCD patients with and without a history of interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 83 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…A study of 11 children with SCD and their caregivers identified 27% of children and 40% of parents with PTSD 40 . Exposure to trauma and post‐traumatic stress symptoms have been identified as risk factors for developing chronic pain, 41,42 including specifically in SCD 43,44 . Research about PTSD and the relationship between trauma and subsequent development of chronic pain is needed for adults with SCD.…”
Section: Anxietymentioning
confidence: 99%
“…A study of 11 children with SCD and their caregivers identified 27% of children and 40% of parents with PTSD 40 . Exposure to trauma and post‐traumatic stress symptoms have been identified as risk factors for developing chronic pain, 41,42 including specifically in SCD 43,44 . Research about PTSD and the relationship between trauma and subsequent development of chronic pain is needed for adults with SCD.…”
Section: Anxietymentioning
confidence: 99%
“…IPV is linked to health problems including chronic pain, frequent headaches, difficulty sleeping, and activity limitations (Black, 2011), as well as musculoskeletal disorders such as degenerative joint disease, low back pain, traumarelated joint disorders, and cervical pain (Bonomi et al, 2009). Individuals with a history of IPV exposure were five times more likely to report chronic pain and six times more likely to report daily use of an opiate-based medication than those with no history of abuse (Ford et al, 2020). Female survivors of IPV during adulthood are almost twice as likely to develop fibromyalgia and chronic fatigue syndrome than those who were not abused (Chandan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%